Fixed point Theorems for Non-self mappings with nonlinear contractive condition in strictly convex FCM-spaces - Mohammad H.M. Rashid (IndoMS, 2020)
In this paper we define convex, strict convex and normal structures for sets in fuzzy cone metric spaces. Also, existence and uniqueness of a fixed point for non-self mappings with nonlinear contractive condition will be proved, using the notion of strictly convex structure. Moreover, we give some examples illustrate our results.